Quantifying the economic and social impacts of high-speed rail: Some evidence from Europe and the People's Republic of China - Chia-lin Chen; Roger W. Vickerman (Asian Development Bank Institute (ADBI), 2019)
In recent years there has been an increasing move towards allowing for impacts beyond the direct user benefits and costs in the appraisal of transport investments. Much of the interest to date has been in justifying the inclusion of such wider impacts as a genuine net addition to a cost-benefit analysis rather than just double counting of direct benefits or displacement effects. The focus has been mainly on the impacts on productivity and economic growth through the impact of increasing accessibility on agglomeration. The paper reviews the arguments in favor of measuring such impacts, the progress made in implementing such impacts in appraisal, and the limitations of such an approach. The paper then proceeds to discuss approaches that analyze the way in which new transport infrastructure may lead to the restructuring and rebalancing of local and regional economies through structural change and the relocation of activities. Evidence from high-speed rail networks in Europe and the People's Republic of China (PRC) is used to examine changes in specialization, the impacts on knowledge-intensive sectors, and new firm formation.
Keywords: L92; R11; R42; R58; 330; transport appraisal; wider economic impacts; agglomeration; economic restructuring